ANALISIS STRATEGI PEMBERDAYAAN MASYARAKAT BERBASIS POTENSI LOKAL MELALUI PROGRAM PENGEMBANGAN MENUJU DESA WISATA PATUGURAN (STUDI KASUS PADA DESA WISATA PATUGURAN) - Bambang Sutikno; Sri hastari; Yufenti Oktavia (Jurnal Cakrawala Ilmiah, 2023)
The tourism village development program is a form of community empowerment program to maximize the village's potential in improving people's welfare. The development of Patuguran village tourism towards a tourist village will have a positive impact on the economic development of local communities by increasing people's income, being able to provide job opportunities and provide additional income for the village government through the collection of levies. This research was conducted to find out the form of community empowerment action in the tourism village development program. This research uses a qualitative approach through case studies. Data collection techniques were carried out by interviews, observation, and document studies. Community empowerment is carried out by optimizing tourism village development programs to become tourism commodities based on local potential in the form of mangrove forests. The development of the Patuguran tourism village, Rejoso sub-district, Pasuruan Regency will provide changes for the community, especially in increasing their knowledge and economy. Therefore, the community empowerment program in Patuguran village can be used as a reference in ecotourism-based community empowerment activities.